Dampak Dari Pengimplementasian Kurikulum K-13 Di SMA S PERTIWI 1 PADANG - Rahma Ega Indriani; Zaky Anshory; Merika; Luthfiani (CV. ITTC INDONESIA, 2024)
Curriculum management plays an important role in improving the quality of graduates in educational institutions. This article discusses strategies and approaches that can be applied in curriculum management to achieve these goals. Through in-depth research and analysis, the author identifies key factors that influence the quality of graduates, such as the relevance of the curriculum to industry needs, improving the quality of teaching and learning, and adapting to technological developments and job market demands. Apart from that, this article also illustrates the important role of managing evaluation and regular curriculum updates in order to maintain accuracy and relevance in facing the dynamics of the ever-evolving educational environment. By implementing effective curriculum management practices, educational institutions can improve the quality of their graduates so that they are better prepared to face challenges in the competitive world of work. The emphasis on curriculum management involves not only appropriate design, but also effective implementation. Good management involves coordination between lecturers, academic administration and other related parties to ensure that the curriculum is well integrated in the learning process.